The Maternal-Fetal Dyad: Exploring the Two-Patient Obstetric Model - Mattingly, Susan S. (The Hastings Center report, 1992)
For ages, medicine has had poor access to the fetus inside the mother's womb. But in relatively recent years, the human body has become transparent. The latest breakthroughs of technology have made it possible, from the very beginning of pregnancy, to consider the fetus as an individual who can be examined and sampled. His or her physician may now establish a diagnosis and prognosis and prescribe a treatment in the same way as in traditional medicine.